2011
DOI: 10.1016/j.conb.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The metamorphosis of the developing cerebellar microcircuit

Abstract: Research highlights► The developing cerebellar circuit exhibits transient synaptic elements. ► Network activity and synaptic plasticity are shaped by such transient circuit elements. ► Transient circuit features may be pivotal in the development of cerebellar circuits. ► The cerebellum is a highly attractive model system for the study of circuit development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 72 publications
(90 reference statements)
1
28
0
Order By: Relevance
“…Therefore it is possible that some developmental factors that are essential for a correct formation of the network are missing. During development, granule cells migrate in the first two postnatal weeks from the external granular cell layer to the internal granule cell layer [49]. This migration is possibly impaired in organotypic slices because we observed in four week old cultures granular cells also near the molecular layer and not only in the internal granule cell layer (data not shown) which could speak for an insufficient maturation of the cerebellar network.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore it is possible that some developmental factors that are essential for a correct formation of the network are missing. During development, granule cells migrate in the first two postnatal weeks from the external granular cell layer to the internal granule cell layer [49]. This migration is possibly impaired in organotypic slices because we observed in four week old cultures granular cells also near the molecular layer and not only in the internal granule cell layer (data not shown) which could speak for an insufficient maturation of the cerebellar network.…”
Section: Discussionmentioning
confidence: 74%
“…Although ultrastructure analysis of disease-related Purkinje cell axonal torpedoes reveals that they do not contain vesicles (Petito et al, 1973; Yagishita, 1978; Mann et al, 1980; Louis et al, 2009), suggesting that they are not presynaptic release sites, we wondered whether developmental Purkinje cell axonal torpedoes might be the presynaptic structure of a transient synapse that functions during postnatal development. Interestingly, Purkinje cells form transient synapses onto other Purkinje cells during postnatal development (Watt et al, 2009), and transient synapses are thought to be a common feature of developing brain circuits (van Welie et al, 2011), and can also be found in other cerebellar neurons (Trigo et al, 2010). To examine whether developmental torpedoes were axon terminals containing vesicles, we used immunolabeling for vesicular GABA transporter (VGAT; Figure 4A ) (Watt et al, 2009), and quantified the number of torpedoes that colocalized with this presynaptic marker ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…The age at which torpedoes occur is a time of great restructuring in the developing cerebellum (McKay and Turner, 2005; van Welie et al, 2011; Hashimoto and Kano, 2013; White and Sillitoe, 2013). Several such transient changes have been identified in developing brain circuits that are thought to be involved in its proper development, including transient depolarization by GABAergic innervation (Ben-Ari, 2001, 2002), and transient electrical synapses (Fulton, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the synaptic and cellular changes observed in developing SCA6 84Q/84Q mice were transient, and these properties were indistinguishable from WT Purkinje cells from weanling (P21–24) mice, an age when climbing fibre and Purkinje cell firing properties have largely matured (McKay & Turner, ; van Welie et al . ; Hashimoto & Kano, ). Our results demonstrate that developmental perturbations do not necessarily cause detectable behavioural abnormalities, and that changes in circuit development may be transient.…”
Section: Introductionmentioning
confidence: 98%